Wages and Wage-Bargaining Institutions in the Emu : A Survey of the Issues - Lars Calmfors (Center for Economic Studies and ifo Institute (CESifo), 2001)
A perceived need to increase nominal wage flexibility as a substitute for domestic monetary policy and a tendency to less wage moderation are likely to promote bargaining co-ordination and social pacts in the EMU. But such co-ordination is not likely to be sustainable in the long run, as it conflicts with other forces working in the direction of decentralization and deunionisation. Although monetary unification will strengthen the incentives for higher-level transnational co-ordination of wage bargaining, such a development is improbable because of the co-ordination costs involved. If transnational co-ordination develops, it is most likely to occur within multinational firms.
Keywords: 330; Wage bargaining; co-ordination; monetary union